Preparation of silica‐supported nanoFe/Ni alloy and its application in viscosity reduction of heavy oil. (1st March 2015) - Liu, Xueliang; Yang, Zhancun; Li, Xiaohong; Zhang, Zhijun; Zhao, Mengyun; Su, Changming
Abstract : Nanozero valent iron and nickel particles of silica composite (SiO2 /Fe/Ni) were prepared via sodium borohydride reduction of ferric chloride and nickel chloride mixed solution in the presence of surface‐modified silica. The prepared nano‐SiO2 /Fe/Ni was characterised by transmission electron microscopy, X‐ray diffraction, Fourier transform infrared spectrometry and Brunauer–Emmett–Teller specific surface area method. It was found that the SiO2 /Fe/Ni, composed of silica with an average size of about 12 nm and zero valent iron and nickel nanoparticles (Fe/Ni) with an average size of several nanometres, exhibited good anti‐oxidation stability, dispersity and phase transfer function. The catalytic effect of SiO2 /Fe/Ni on the Shengli extra‐heavy oil was evaluated at a low temperature and the sulphur content of heavy oil before and after aquathermolysis was analysed by an elemental analyser. Results have revealed that the SiO2 /Fe/Ni has good catalytic performance in the aquathermolysis process of heavy oils. In particular, at the condition of mass fraction of 0.5% and reaction temperature of 150°C for 48 h, it could significantly reduce the viscosity of heavy oil from 184 to 42 Pa·s. When compared with the original heavy oil sample the viscosity reduction rate was 77.17%, showing promising potential in the industrial production of heavy crude oils.